(untitled) (Majalah Kedokteran Bandung, 2019)
Rituximab is a chimeric monoclonal antibody which has specific for CD20 antigen expressed by pre-B and mature B-cells. Radiolabelled Rituximab, 131I-Rituximab, has been sucessfully used for treatment of B-Cell NHL. Due to its short shelf-life, 131I-Rituximab is commonly freshly prepared in hospitals prior to its used. This study aimed to validate rituximab iodination procedure for 131I-Rituximab preparation in order to find the most suitable procedure to be applied in hospitals which intend to produce 131I-Rituximab in-house. Three different methods of radiolabelling using three types of oxidizing agents, namely Iodobeads, Iodogen, and Chloramine-T were performed. Prior to the validation, radiochemical purity test and purification procedures were also validated as these procedures are critical for producing an acceptable quality of I-Rituximab. In addition, the shelf-life of 131I-Rituximab was also studied. This study was conducted at the Centre for Radioisotope and Radiopharmaceutical Technology, Serpong during the period of July 2015 to February 2018. The results showed that the radiochemical purity test of 131I-Rituximab could be easily performed by using instance thin layer chromatography–silica gel (ITLC-SG) in the stationary phase and 85% methanol or saline in the mobile phase. Purification of 131I-Rituximab was conducted using a Sephadex G-25 M filled column with 0.1 M PBS, pH 7.2, as the eluent that was found to be quite reliable to give 131I-Rituximab with radiochemical purity of >95% and recovery of approximately 90%. Radiolabelling efficiency performed using Iodobeads was the lowest (60%) compared to that of Iodogen and Chloramine-T (80–90%). In addition, approximately 30% of I was retained by Iodobeads and this procedure was time consuming( 1 hours). It is concluded that Chloramine-T and Iodogen are better than Iodobeads as the oxidizing agent for radiolabelling of Rituximab with 131I. The radiochemical purity of 131I-Rituximab is well maintained when stored at room temperature and in 4 °C temperature up to 6 hours. Validasi Prosedur Iodinasi Rituximab untuk Preparasi131 I-Rituximab Validasi proseduri odinasi rituximab untuk preparasi131I-Rituximab telah berhasil dilakukan. Validasi ini dilakukan untuk mendapatkan prosedur yang paling sesuai yang dapat diaplikasikan untuk produksi131 I-Rituximabdi rumah sakit yang ingin memproduksi131 I-Rituximab di laboratorium mereka. Tiga metode radiolabelling menggunakan 3 jenis oksidator Iodobeads, Iodogen, dan Chloramine-T telah divalidasi. Sebelum validasi ini, prosedur uji kemurnian radiokimia dan pemurnian divalidasi terlebih dahulu karena prosedur-prosedur ini sangat berpengaruh dalam penyediaan131 I-Rituximab dengan kualitas yang baik. Disampingitu, lama simpan131I-Rituximab juga dipelajari. Penelitan ini dilaksanakan di Pusat Teknologi Radioisotop dan Radiofarmaka, Serpong, Juli 2015–Februari 2018. Hasil penelitian memperlihatkan bahwa uji kemurnian radiokimia 131I-Rituximab dapat dilakukan dengan mudah menggunakan instance thin layer chromatography – silica gel (ITLC-SG) sebagai fasa diam dan metanol 85% atau larutan salin sebagai fasa gerak. Pemurnian131I-Rituximab menggunakan kolom Sephadex G-25 M dan0.1 M PBS pH 7,2 sebagai eluen dapat diandalkan dan memberikan131I-Rituximab dengan kemurnian radiokimia >95% dan sekitar 90% perolehan kembali. Efisiensi penandaaan menggunakan Iodobeads didapatkan paling (60%) dibanding dengan Iodogen dan Chloramine-T (80 – 90%). Di samping itu, sekitar 30% 131I hilang karena terikat pada Iodobeads dan prosedur ini memakan waktu yang panjang ( 1 jam). Penandaan Rituximab 131I menggunakan Chloramine-T and Iodogen dapat disimpulkan lebih baik dibanding dengan menggunakan Iodobeads. Kemurnian radiokimia131I-Rituximab terjaga dengan baik pada penyimpanan selama 6 jam pada suhu kamar dan 4 °C.